2017
DOI: 10.15741/revbio.04.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: La expansión de la agricultura en el mundo ha provocado, entre otras cosas, el incremento en By performing an analysis of the possible applications and use advantages, and the possible risks to health and the environment, it is concluded that doubt and existing limitations in current knowledge on the exposure and effects in organisms, including the human being, are wide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Pure propiconazole was obtained as a colorless oil containing both diastereoisomers. First diastereoisomer 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure propiconazole was obtained as a colorless oil containing both diastereoisomers. First diastereoisomer 1…”
Section: Resultsmentioning
confidence: 99%
“…This encouraged the intensive use of pesticides, many of which are synthetic and with a very high efficiency. Nevertheless, as time went by, there have been observed serious environmental effects as a consequence of the use of such chemicals [1]. Due the continuous growth of the population, there is a critical necessity of getting a better food production and maintain the food safety worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of nanopesticides have been quoted in published literature (Kah et al, 2013;Perlatti et al, 2013;Kah and Hofmann, 2014;Kookana et al, 2014;Cano Robles and Mendoza Cant u, 2017). However, a clear and agreed definition of nanopesticide is currently not available, 37 and many of the publications have regarded products containing particles ranging from the typical nanoscale (between 1 and 100 nm) to much larger sizes (up to 1,000 nm) as nanopesticides.…”
Section: E2 Recommended Guidance For Nanomaterials Pesticidesmentioning
confidence: 99%
“…This literature search also resulted in the highest number of records for nanoencapsulates, silver and titanium dioxide and showed that food additives and FCM are the most frequently indicated applications. Future developments are expected in the field of nanoencapsulates and nano-composites in applications such as novel foods, food/feed additives, biocides, FCM, and especially pesticides (Kah et al, 2013;Perlatti et al, 2013;Kah and Hofmann, 2014;Kookana et al, 2014;Cano Robles and Mendoza Cant u, 2017;Chaudhry et al, 2017). As mentioned in the conclusions of the 2011 SC Guidance, it will require updating to stay aligned with innovations and fast developments in this area.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation